SYNERGISTIC EFFECT BETWEEN THIOL COLLECTORS IN REACTION WITH SULPHIDE MINERALS (Biological Sciences - PJSIR, 2001)
The study of synergism between potassium ethyl xanthate (Ketx) and sodium diethyl dithiocarbamate (Dtc) in reactionwith heazlewoodite (Ni3S2) is described. It has been demonstrated that its occurrence can be explored by simple cyclicvoitametry and adsorption measurements. Correlation was obtained between flotation recoveries, adsorption isothermsand cyclic voitametry measurements. The maximum synergistic effect between Ketx and Dtc was observed at the ratioof 0.35:0.65.